A comparative analysis of the work environments for registered nurses, nurse aides, and caregivers using the 5th Korean Working Conditions Survey - Sung Shin Kim; Yun Jin Kim; Jun Sik Park; Seoung Hee Ho; Hyosun Kweon; Young-Hyeon Bae (BMC, 2022)
Abstract Background Since the quality of work life of healthcare workers is affected by various factors, an improvement in their work environment can reduce the burden on them, increasing their performance. This study aimed to identify the current problems in working environments for registered nurses (RNs), nurse aides (NAs), and caregivers using the 5th Korean Working Conditions Survey (KWCS), presenting measures to improve working conditions by analyzing their predictors: 1) degree of exposure to work-related risk factors (musculoskeletal and mental), 2) working patterns, 3) work-family balance, 4) work situations, and 5) self-rated health. Methods The sampling frame was a list of apartment and general survey zones, excluding islands, dormitories, special social facilities, tourist hotels, and foreigner zones, among the total survey zones of the 2010 Population and Housing Census. The KWCS was given to 50,205 participants of various occupations, and responses from 494 RNs, 201 NAs, and 505 caregivers were extracted to compare their 1) degree of exposure to work-related risk factors (musculoskeletal and mental), 2) working pattern, 3) work-family balance, 4) work situations, and 5) self-rated health. Results The response rate was 0.449. There were significant differences in all the variables (exposure to musculoskeletal and mental work-related risk factors, working pattern, work-family balance, work situations, self-rated health, and satisfaction with working conditions) among RNs, NAs, and caregivers (p < 0.001). The degree of work-related musculoskeletal and mental risk exposure was higher among caregivers and RNs than among NAs; irregular working patterns, challenges with work-family balance, and work environment satisfaction were higher among caregivers than among NAs. In addition, work situations were poorer among caregivers and NAs than among RNs. Self-rated health was the highest among caregivers, followed by RNs and NAs. The most potent predictor of self-rated health was occupation, followed by work environment satisfaction and work-family balance; the most potent predictor of work environment satisfaction was self-rated health, followed by degree of exposure to work-related musculoskeletal and mental risk factors, occupation, work-family balance, work situation, and working patterns. Conclusion This study confirmed that a variety of factors influence work environment satisfaction. Thus, practical and realistic measures to improve work environments tailored to each healthcare occupation should be developed at the national and community levels. Further qualitative studies are needed to analyze the work environments of nurses and other care workers in depth.